Propriedades terapêuticas de Anredera cordifolia nas doenças crônicas não transmissíveis: revisão de escopo - Trombini, Fernanda dos Santos (2023)
The present study consists of a scoping review and has as a general objective to map the properties of the plant Anredera cordifolia in the therapeutic process of Chronic Noncommunicable Diseases in laboratory studies with human beings, animals and cellular models. The specific objectives are to identify the therapeutic properties of the plant Anredera cordifolia; and to specify the areas of knowledge that have developed studies with the plant Anredera cordifolia. The scoping review began with the development of a protocol, which in this study was developed based on the Joanna Briggs Institute guidelines and registered on the Open Science Framework platform. The review question was: What are the properties of the plant Anredera cordifolia in the therapeutic process of Chronic Noncommunicable Diseases in laboratory studies with humans, animals and cellular models? The selection criteria were: experimental studies in the laboratory context with human beings, animals and/or cellular models; studies that address the properties of the plant Anredera cordifolia in the therapeutic process of Chronic Non-Communicable Diseases; primary studies of the experimental type, developed in a laboratory context; studies published in any language. No geographic or temporal delimitation was established. The search was performed in the Medline/Pubmed, Scopus, Web of Science, and CINAHL data sources in July and August 2022. Rayyan software was used to manage the references. The data were subjected to coding and content analysis. The sample consisted of 25 articles, predominantly published in English and in the period from 2011 to 2022. All studies were developed in Asia and most were in the field of pharmacology. The scientific evidence showed that the plant had positive effects in the treatment of diabetes mellitus, hypertension, chronic kidney disease, obesity, and cataract, besides having beneficial effects in controlling cholesterol, triglyceride, and uric acid levels. The main therapeutic effects identified were hypoglycemic effect and decrease in serum levels of triglycerides and total cholesterol. It is worth mentioning that the plant also has beneficial effects on the healing of diabetic wounds, on the reduction of blood pressure and heart rate, on obesity, with the inhibition of body weight or reduction of the fat layer, on the reduction of creatinine levels, on the reduction of serum urea concentration and renal index, and increasing the level of catalase. The absence of studies in the nursing field and of research developed in Brazil was evidenced. It is expected that this review will contribute to the development of new research, suggesting that the theme be researched in different continents, by new researchers, and that new studies on the theme be carried out by nursing researchers.